Exploring the Entrepreneurial Intention-Competency Model for Nascent Entrepreneurs: Insights From a Developing Country Context - Botha, Melodi; Taljaard, Amorie (Frontiers in Psychology, 2021)
Some previous scholars have investigated the relationship between entrepreneurial intention (EI) and entrepreneurial competencies (ECs), yet categorising individual ECs in relation to higher order competence constructs have not been explored. Based on previous literature, four higher order constructs are identified, namely: Cognitive, Functional, Social/Personal and Meta-competence. Investigating which ECs are categorised according to the four higher order constructs in this relationship with EI, is important as it contributes to the development and training of these antecedents of entrepreneurial behaviour. Data is collected from 203 nascent entrepreneurs in South Africa and analysed using Structural Equation Modelling (SEM). In this developing country context, only two higher order constructs, Cognitive/Functional competence and Social/Personal competence fit the data in the relationship with EI. The strongest positive relationships were found between the Cognitive and Functional higher order construct and opportunity recognition, opportunity assessment, conveying a compelling vision and creative problem solving. The cognitive and functional higher order competence construct also showed a strong positive relationship with EI. To improve pedagogical interventions and enhance EI, educators and policy makers can use these findings in entrepreneurship programmes to ensure that this higher order competence construct with the individual ECs in this category, are developed simultaneously rather than individually. Research efforts and support programmes that include cognitive and functional higher order competence constructs for nascent entrepreneurs should therefore not be neglected. Such efforts and programmes can encourage EI which in turn can enhance entrepreneurial behaviour, which could contribute to economic growth and employment creation.